Examining the use of media advocacy by civil society organisations in democratizing youth participation in local governance structures: a case of Youth Empowerment and Transformation Trust Project in Masvingo, Chitungwiza and Makonde - Usaiwevhu, Itayi (Midlands State University, 2018)
The demographic analysis shows that young people constitute the majority of the population yet, are underrepresented in democratic structures. Civil society organizations have made attempts to increase youth participation in the broader framework of enhancing citizen participation. The study therefore looks at ways Youth Empowerment and Transformation Trust (YETT) as representative of civil society organizations is using media advocacy in increasing youth participation with a critical look at the factors and relationship between effectiveness of interventions and traceable increase of democratic youth representation. YETT is a networking youth organizations committed to the full participation of young people in sustainable development through advocacy and capacity building. Conversations with the YETT project leaders are verified with discussions with participants from the project areas in combination with scientific analysis of trends, opinions and attitudes to realize the contribution of media advocacy towards democratic participation. Resultantly, the enquiry shows that the basis of democratic participation of young people is rights which must make use of means of communication that are most appropriate to the youths. In addition, it is empowering for inclusive participation and active involvement of young people throughout the communication process. A suitable model that utilizes a combination of traditional means of communication and features of new media is necessary to sustain advocacy efforts.